Combined Arthroscopic Anterior Cruciate Ligament Reconstruction and Distal Femoral Osteotomy in a Patient of Bilateral Genu Valgum – A Rare Case Report - Parthasarathi Das; Soumitesh Sibananda Das (Journal of Orthopaedic Case Reports)
Introduction: Anterior cruciate ligament (ACL) injury sometimes is associated with genu valgum. Valgus malalignment poses concerns due to its potential to increase strain on the ACL, thereby elevating the risk of osteoarthritis in the lateral compartment of the knee. However, lacune still exists regarding the concomitant reconstruction of ACL and distal femoral osteotomy in ACL-deficit knee with genu valgum. The present case report aims to fill this gap by presenting a rare case of a young patient with a symptomatic ACL deficit knee and femur-originated genu valgum. Case Report: A young male presented with bilateral genu valgum at our clinic with pain and instability of the right knee following a sports injury for 1 year. The anterior drawer, Lachman, pivot shift, and McMurray test were positive in physical examination. The surgical intervention comprised lateral open wedge osteotomy of the distal femur, all-inside reconstruction of the ACL, and partial meniscectomy for the meniscal tear. Conclusion: Simultaneous ACL reconstruction with femur osteotomy offers favorable outcomes in patients presenting with genu valgum. This integrated approach minimizes hospitalization and rehabilitation periods. Meticulous planning and surgical techniques, including careful femoral tunnel placement, can mitigate potential complications like plate interference.